Preparing the pre-service teachers to meet the teacher qualification standard: Potencies and challenges - Ragawanti, Debora Tri (Proceeding of International Conference on Teacher Training and Education, 2016)
To response to challenges of teaching English for communication, teacher education programs are urged to prepare the student-teachers to meet the challenges. As a part of the preparation, an evaluation on the studentâs performance before they graduate is necessarily to be done. This study attempts to weigh up theÂ  capacity of student-teachers from the English teacher education Program, Satya Wacana Christian University, Indonesia using the teacher qualification standard. This involved 26 mentor-teachers from 10 local schools where the student-teachers were doing teaching practicum. The findings from the questionnaire and interview interestingly revealed that the student-teachers are viewed to be good in performing pedagogical knowledge (2.92), pedagogical skills (2.86), personality (3.27), social (3.17), and professional competence (3.10). Apart from the opportunities, teachers, curriculum designers, and policy makers will be taken to examine theirÂ  challenges in meeting the standardÂ  and to consider the proposal on what a teacher education can do to improve the pre-service teachers capacity to teach English.